Hubungan Faktor Karakteristik Petugas Terhadap Kepuasan Sistem E-Puskesmas di Puskesmas Kecamatan Tambora - Nazira Nur Amalia; Daniel Happy Putra; Puteri Fannya (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2024)
Evaluation of information system performance depends on the level of satisfaction shown by users of the system. End User Computing Satisfaction (EUCS) is a system evaluation method used to assess the extent to which a system is considered valuable in terms of user satisfaction. This research was conducted with the aim of finding out the correlation between employee demographic factors, especially age, education level and gender, and their level of satisfaction with the use of the E-Puskesmas system at the Tambora District Health Center. This research was conducted at the Tambora District Health Center, west of Jakarta using an inferential analytical research approach with a sample size of 98 participants. The results obtained from examining the age of respondents using the chi-square test showed that there was no relationship between age and user satisfaction with the E-Puskesmas system. User satisfaction using the EUCS construct, 56.1% were satisfied with the existing system, while 43.9% of users were still not satisfied with the E-Puskesmas system at the Tambora District Health Center. The results of the chi square test on user satisfaction based on gender showed that the P-Value value was 0.627, which was greater than <0.05, indicating that there was no relationship between gender and satisfaction with using the E-Puskesmas system.